Surprise Authorship, Credit, and Responsibility - Meyer, Albert R; Whitbeck, Caroline (Online Ethics Center, 2006)
A scenario dealing with issues of authorship, credit, and responsibility as pertaining to graduate students.
Open-ended scenario
Keywords: Collaboration; Mentors and Trainees; Publication Ethics; Research and Practice